Understanding of the Mental Capacity Act in work with older adults exploring the "unintended consequences" for service users' emotional wellbeing. Issue 3 (12th September 2016) - Graham, Matthew
Abstract : Purpose: The purpose of this paper is to explore the consequences for older people's mental wellbeing of understandings relating to the Mental Capacity Act 2005 (MCA). The MCA seeks to maximise people's abilities to make decisions and provides a framework for decisions to be made in a person's best interests should they lack the mental capacity to do so themselves (Graham and Cowley, 2015). Practice varies widely amongst health and social care practitioners and little is known about the nature of interventions under the MCA or the outcomes for service users' lives and health, especially their mental health and emotional wellbeing. Design/methodology/approach: By reflecting upon existing evidence this position paper offers a narrative of how practice in applying the principles of the MCA may impact upon the mental wellbeing of older people. Drawing upon court of protection judgements and existing research the author analyses the way the MCA is understood and applied and how institutional mechanisms might hinder good practice. Findings: There are tensions between policy imperatives and examples of practice linked to the MCA, the spirit of the MCA and tenets of good practice. Despite efforts on promoting choice, control and rights there is growing paradoxical evidence that the MCA is used as a safeguarding tool with the consequences that it constrains older people's rights and that it may encourage risk averse practice. The consequences of this for older people are considerable and include lack of choice, autonomy and self-determination. This discussion suggests that anxiety in relation to the application of the MCA stills exists in practice and that maximising older people's capacity and supporting decision making is central in promoting mental health and wellbeing. Practical implications: This position paper will identify how the MCA might be interpreted in action through consideration of existing evidence. This paper may lead to future research on how understandings of the MCA are constructed and what values underpin its application from conception to outcomes in relation to understandings of risk, risk aversion, decision making and the potential and need for emancipatory practice. Essentially, the paper will discuss how the MCA actually seeks to enhance the mental health and emotional wellbeing of older adults by offering a rather radical approach to understanding people's wishes and feelings, but how attitudes may lead to misunderstandings and negative outcomes for the individual. Originality/value: In a climate of serious case reviews identifying concerns and abuses in care it is imperative that understanding of the MCA inform good practice. However, what constitutes good practice requires unravelling and the agendas, requirements and attitudes of interventions need considering from an epistemological perspective as well as to project how the outcomes of decision-making impact upon the mental health of older adults. This paper will discursively add value to the narrative around how the MCA is applied in practice and how chosen practice often constructs the mental wellbeing of older adults.